Adsorption of L-lysine on montmorillonite - Parbhakar,A; Cuadros,J; Sephton,MA; Dubbin,W; Coles,BJ; Weiss,D (COLLOID SURFACE A, 2007)
Amino acid adsorption on smectite is relevant to prebiotic processes involving possible catalytic reactions in the early Solar System, as implied by the clay-organic correlation found in meteorites, and the generation and modification of organic components essential for the origin of life. Here we report the results of a study investigating the adsorption of l-lysine (0.025–0.4 M) onto montmorillonite. The reaction products were studied using X-ray diffraction, chemical analysis and infrared spectroscopy.We find that lysine adsorption is first dominated by cation exchange and then by adsorption of electrically neutral lysine (as a zwitterion), as indicated by chemical and FTIR evidence. At the maximum concentration, lysine displaces only ∼1/3 of the original interlayer cations. The d-spacing of the smectite–lysine complex increases from 1.2 to 2.1 nm as more lysine enters the interlayer space, and water is expelled. We propose a structural model of lysine sorption in the interlayer in which lysine is oriented at >45–90 to the plane of siloxane O atoms.